2006
DOI: 10.1097/01.gme.0000198491.34371.9c
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hormone therapy with and without methyltestosterone augmentation of venlafaxine in the treatment of postmenopausal depression: a double-blind controlled pilot study

Abstract: Methyltestosterone 2.5 mg had the highest effect size compared with placebo, but the high dropout rate prevented its efficacy from being determined. Estrogen plus medroxyprogesterone, combined with methyltestosterone or otherwise, demonstrated a trend toward increased efficacy of venlafaxine. Further larger-scale clinical trials are needed to elucidate the findings of this pilot study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…An initial open-label study on estrogen augmentation showed positive results [124], and 1 small placebo-controlled study on perimenopausal women who had partly responded to SSRI treatment found a benefit from adjunctive estrogen [125]. However, another augmentation study found improvement with testosterone, but not with progesterone or estrogen plus progesterone [126]. …”
Section: Resultsmentioning
confidence: 99%
“…An initial open-label study on estrogen augmentation showed positive results [124], and 1 small placebo-controlled study on perimenopausal women who had partly responded to SSRI treatment found a benefit from adjunctive estrogen [125]. However, another augmentation study found improvement with testosterone, but not with progesterone or estrogen plus progesterone [126]. …”
Section: Resultsmentioning
confidence: 99%
“…A preliminary study of methyltestosterone as augmentation of venlafaxine in the treatment of postmenopausal women with depression showed promising results. 9 However, this study did not investigate the effects of this therapy in women with refractory depression. We hypothesized that low-dose testosterone therapy would be an effective augmentation therapy in women with treatment-resistant depression and conducted an open-label pilot study to investigate this hypothesis.…”
Section: Introductionmentioning
confidence: 95%
“…These antidepressants were selected on the bases of their mechanism of action, FLX as a SSRI, DMI as a NaRI, and VLX as a mixed 5-HT/NA reuptake inhibitor. In addition, VLX has been proposed to have a shorter latency of action and is a useful drug for the treatment of clinical depression in women (Carrol 2006;Dias et al 2006).…”
Section: Introductionmentioning
confidence: 99%